Subcutaneous Administration of Otelixizumab is Limited by Injection Site Reactions: Results of an Exploratory Study in Type 1 Diabetes Mellitus Patients - MacDonald, A.; Ambery, P.; Donaldson, J.; Hicks, K.; Keymeulen, B.; Parkin, J. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Targeting CD3 antigens on human T lymphocytes with monoclonal antibodies has been shown to reduce the rate of decline of C-peptides in recent-onset type 1 diabetes mellitus patients. However, effective doses are associated with infusion reactions typical of “cytokine release syndrome” and appear to be dose-limiting when administered as short-duration infusions. A possible alternative approach, which may reduce the rate of T cell activation and consequent systemic cytokine release, is to inject subcutaneously. We investigated single- and repeat-dose subcutaneous administration of the anti-CD3 monoclonal antibody otelixizumab in small cohorts of patients with type 1 diabetes. Transient reductions in free or unbound CD3 antigen on CD4+ and CD8+ cells and absolute lymphocyte count were observed in the blood of these patients during treatment, consistent with the known mechanism of action of otelixizumab and other anti-CD3 monoclonal antibodies. This was despite the very low systemic exposure of antibodies measured during the same time period. With the exception of sporadic headaches, other symptoms associated with cytokine release syndrome, such as fever, nausea, vomiting, myalgia, and arthralgia, were absent in treated patients. However, treatment-related injection site reactions were consistently observed. The reactions were erythematous and their sizes were dose-dependent; in some cases, reactions persisted for up to 2 weeks following the start of treatment. While patients responded well to topical corticosteroid treatment and prophylaxis reduced the intensity of injection site reactions, the reactions were considered dose-limiting and higher doses were not investigated.
Keywords: cytokine release; safety; pharmacokinetics; pharmacodynamics; anti-CD3